RADIOLOGICAL FINDING IN CHRONIC OSTEOMYELITIS - Nopriantha, Made (E-Jurnal Medika Udayana; vol 2 no 8 (2013):e-jurnal medika udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Osteomyelitis is a bone disease, it is characterized by infection of bone marrow and adjacent bone , and often associated with cortical and trabecular destruction. There are many imaging modalities that we can be use to diagnose chronic osteomyelitis include plain radiography, ultrasonography, nuclear imaging, CT scan and MRI. Although plain radiography still accurately shows chronic changes, CT scan is more sensitive for the detection of sequestra, sinus tract and soft tissue abcess. Both CT and Ultrasound are usefull for guiding percutaneus aspiration of subperiosteal and soft tissue abscess or fluid collection . Sequential technetium and gallium or indium scans may help determine wh e ter infect i on is active and may distinquish infection from noninflammatory bone changes. MRI provides superior information about the anatomical extent of infection but does not always distinguish osteomyelitis from healing fractures and tumors. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: chronic osteomyelitis, plain photo, CT-Scan